SEFT and Academic Stress on Nursing Students in Online Learning During the Covid-19 Pandemic - Ayu Dewi Nastiti; Erik Kusuma; R.A. Helda Puspitasari; Dwining Handayani (Jurnal Ilmu Keperawatan Jiwa, 2022)
The occurrence of the COVID-19 pandemic has made many changes in the education sector which has turned to online learning. Changes in the system trigger the emergence of academic stress on students which will have an impact on their learning achievement . This study aims to determine the effect of the SEFT method on reducing the level of academic stress experienced by students. The research design used in this study was pre-experimental with a one group pre-post test design approach , with 250 research subjects who were active students of the D3 Nursing Study Program, Unej Campus, Pasuruan City. Statistical test results using the Wilcoxon Signed Rank Test with = 0.05 resulting in a significance value of 0.001 which means that there is a difference in scale before and after SEFT therapy. It was concluded that SEFT therapy was considered effective in reducing academic stress on students of the D3 Nursing Study Program, Unej Campus, Pasuruan City.